Methodological approach towards sustainability by integration of environmental impact in production system models through life cycle analysis: Application to the Rioja wine sector. (February 2014) - Jiménez, Emilio; Martínez, Eduardo; Blanco, Julio; Pérez, Mercedes; Graciano, Charmery
This paper proposes the integration of life cycle analysis within the production system models as a tool for decision making (whether at the strategic, tactical or operational levels) attending not only economic and technical criteria but also the environmental impact. This methodological proposal advances over the traditional approach of calculating the value of the environmental impact of a particular product, by proposing the use of models to determine the environmental impact of the product, according to the decisions made in the production system. That is, it does not provide an impact value of the product, but rather a model to determine the impact in terms of the decisions made in the production process; therefore, it can be used, especially by means of simulation, for the optimization of the production system, based on multiple criteria (including environmental impact). The methodological approach is exemplified by a case study, which is used to validate the proposal and to expose it more precisely and clearly, although the methodology is equally applicable to any production process, especially processes highly automated or with different alternative production techniques. This case study, based on the wine production sector of the Rioja Qualified Designation of Origin, in Spain, was made with actual data after several years of research in representative wineries; therefore, besides an application example, it is a support tool for sustainability in wineries, by reducing the environmental impact of wine production (especially in La Rioja and Spain, but generally throughout the world).